DNA-Plasmid Extraction Of Salmonella Isolated From Raw Milk - Nazal, Khulood K. (The Iraqi Journal of Veterinary Medicine, 2008)
Twenty five Isolates of Salmonella were isolated from raw milksamples which were collected from Abu-Graib village to study therelationship between their resistance to antibiotics and their plasmidscontents .Antibiotic sensitivity test for different antibiotics revealed that mostSalmonella isolates were resistant to two antibiotics .The extraction of the DNA-plasmid revealed that most Salmonellaisolates which resistant to two antibiotics or more were contained large,individual plasmids size of (55-75)Kilo Base (KB) while the othersisolates were free from such plasmid